Granulocyte-colony stimulating factor attenuates mitochondrial dysfunction induced by oxidative stress in cardiac mitochondria - Savitree Thummasorn (2018)
During cardiac ischemia-reperfusion injury, reactive oxygen species (ROS) level is markedly increased, leading to oxidative stress and mitochondrial dysfunction. Although granulocyte-colony stimulating factor (G-CSF) is known to be cardioprotective, its effects on cardiac mitochondria during oxidative stress have never been investigated. In this study, we discovered that G-CSF completely prevented mitochondrial swelling and depolarization, and markedly reduced ROS production caused by H2O2-induced oxidative stress in isolated cardiac mitochondria. Its effects were similar to those treated with cyclosporine A and 4'-chlorodiazepam. These findings suggest that G-CSF could act directly on cardiac mitochondria to prevent mitochondrial dysfunction caused by oxidative stress. © 2011 Elsevier B.V. and Mitochondria Research Society. All rights reserved.